Learning climate, basic need satisfaction, perceived choice, study engagement, and students’ performance - Hassan, Arif (2013)
The paper examines the role of learning climate (autonomy supportive vs. controlling), intrinsic motivation resulting from the three basic needs satisfaction (as posited by Self Determination Theory of motivation), self-perception of choice and self-awareness on students’ study engagement and academic performance (measured in terms of CGPA). The study intended to test the validity of Self Determination Theory (SDT) in the Asian and Islamic cultural and institutional context. The data were collected from 529 undergraduates Muslim students (Females = 57.7% and 81.7% Malaysians) representing several study disciplines. Standardized instruments were employed to measure the constructs of learning climate, basic needs, perceived self-determination, and study engagement. Results provided strong support to the SDT proposition suggesting that an autonomy supportive learning climate significantly contributed to intrinsic need satisfaction of autonomy, competence, and relatedness. It was also found that the autonomy supportive learning climate and satisfaction of competency need contributed to study engagement. However, other than the relatedness need satisfaction which contributed negatively to students’ academic performance, no other factor was associated with students’ CGPA. Obviously performance is the result of a number of other factors such as ability, besides motivation. The study provides good empirical support to the SDT propositions from a non-Western cultural context.